Actions versus Prospects: The Effect of Problem Representation on Regret - Harless, David W. (American Economic Review, 1992)
Suppose that you must choose between lotteries S (safer) and R (riskier) shown in the top half of Figure 1. There are 100 possible states of the world and the consequence of S and R are indicated for each state. The states of the world with the consequence win are separate from the states with the consequence win $20,000. You may find S less appealing knowing that if you choose it and one of the states 71-100 occurs you would have received $20,000 had you picked R. Suppose that you must choose between lotteries S' and R' shown in the bottom half of Figure 1. Though the prospects (probability distribution of consequences) of S' and R' are identical to those of S and R, the states of the world with positive payoffs overlap. You may find S' more appealing knowing that if you choose it and one of the states 1-30 occurs you would have received $20,000 had you picked R', but S' pays an $8,000 consolation prize. A series of papers by Graham Loomes (1988a, b, 1989) and Chris Starmer and Robert Sugden (1989) provides evidence that in evaluating identical prospects the juxtaposition of consequences against different states of the world has a systematic effect on choice under as predicted by regret theory (David E. Bell, 1982; Peter C. Fishburn, 1982; Loomes and Sugden, 1982, 1987a). Regret effects violate expected utility theory and all other prospect-based theories of choice. All of the laboratory evidence of regret or juxtaposition effects, however, has been generated under the problem representation in Figure 1: the matrix of state-contingent consequences. While Loomes (1988b p. 468) argues that evidence of regret effects indicates that prospect-based theories ...may all be failing to capture an important element in decision making under uncertainty, this paper suggests that the experimental evidence of regret effects observed so far is specific to the matrix-problem representation. Nearly 400 subjects completed versions of two questionnaires in which choice problems were presented in different formats. The juxtaposition of consequences sways choices, but only under the matrix presentation. The first questionnaire indicates that regret effects are not observed when statecontingent consequences are described by ticket numbers, rather than a matrix. The second questionnaire indicates that if the matrix format is changed slightly to a simple proportional format subjects apparently compare prospects and ignore the juxtaposition of consequences. Regret theory predicts that choice depends on the juxtaposition of consequences, but regret effects should be invariant to different representations of state-contingent consequences.